A Conspectus of the Araceae of Sabah - Jyloerica, Joling (Universiti Malaysia Sarawak (UNIMAS), 2021)
There are limited systematic studies on Araceae in Sabah. This study was started by compiling data from various herbaria (US, UPM, SNP, SING, SAR, SAN, PNH, P, NSW, MO, M, L, KYO, KRB, KEP, K, E, C, BRUN, BORH, BO, AAU, AAH, AA and A) to access the Araceae diversity in Sabah based on herbarium collections. An updated checklist of Araceae in Sabah includes 30 genera and 104 described species. The 30 genera of Araceae in Sabah (24 described genera and 6 missing genera) are: Aglaonema Schott, Alocasia (Schott) G.Don, Amorphophallus Blume ex Decne., Amydrium Schott, Anadendrum Schott, Arisaema Mart., Bucephalandra Schott, Colobogynium Schott, Colocasia Schott, Cryptocoryne Fisch. ex Wydler, Cyrtosperma Griff., Epipremnum Schott, Gamogyne N.E.Br., Homalomena Schott, Lasia Lour., Lemna L., Nabalu S.Y.Wong & P.C.Boyce, Ooia S.Y.Wong & P.C.Boyce, Phymatarum M.Hotta, Pistia L., Pothos L., Pursegloveia S.Y.Wong, S.L.Low & P.C.Boyce, Rhaphidophora Hassk., Rhynchopyle Engl., Schismatoglottis Zoll. & Moritzi, Scindapsus Schott, Spirodela Schleid., Tawaia S.Y.Wong, S.L.Low & P.C.Boyce, Typhonium Schott and Wolffia Horkel ex Schleid. From the list, three genera (Cryptocoryne, Phymatarum and Pursegloveia) are new generic records. Cryptocoryne ciliata and Pothos leptostachyus are new records for Sabah. Homalomena portae-inferni, Pothos fractiflexus and Pursegloveia imbakensis are newly described species for Sabah. Tawaia is a monospecific genus endemic to Sabah. There are 49 species of Araceae that are Sabah endemics. A preliminary result of the IUCN Red List status and distribution map is also included for all the species of Araceae in Sabah.